Improving child survival through a district management strengthening and community empowerment intervention: early implementation experiences from Uganda - Katahoire, Anne R.; Kiwanuka, Dorcus H.; Ssegujja, Eric; Waiswa, Peter; Ayebare, Florence; Bagenda, Danstan; Mbonye, Anthony K.; Peterson, Stefan S. (BMC public health, 2015)
Background: The Community and District Empowerment for Scale-up (CODES) project pioneered the implementation of a comprehensive district management and community empowerment intervention in five districts in Uganda. In order to improve effective coverage and quality of child survival interventions CODES combines UNICEF tools designed to systematize priority setting, allocation of resources and problem solving with Community dialogues based on Citizen Report Cards and U-Reports used to engage and empower communities in monitoring health service provision and to demand for quality services. This paper presents early implementation experiences in five pilot districts and lessons learnt during the first 2 years of implementation. Methods: This qualitative study was comprised of 38 in-depth interviews with members of the District Health Teams (DHTs) and two implementing partners. These were supplemented by observations during implementation and documents review. Thematic analysis was used to distill early implementation experiences and lessons learnt from the process. Results: All five districts health teams with support from the implementing partners were able to adopt the UNICEF tools and to develop district health operational work plans that were evidence-based. Members of the DHTs described the approach introduced by the CODES project as a more systematic planning process and very much appreciated it. Districts were also able to implement some of the priority activities included in their work plans but limited financial resources and fiscal decision space constrained the implementation of some activities that were prioritized. Community dialogues based on Citizen Report Cards (CRC) increased community awareness of available health care services, their utilization and led to discussions on service delivery, barriers to service utilization and processes for improvement. Community dialogues were also instrumental in bringing together service users, providers and leaders to discuss problems and find solutions. The dialogues however are more likely to be sustainable if embedded in existing community structures and conducted by district based facilitators. U report as a community feedback mechanism registered a low response rate. Conclusion: The UNICEF tools were adopted at district level and generally well perceived by the DHTs. The limited resources and fiscal decision space however can hinder implementation of prioritized activities. Community dialogues based on CRCs can bring service providers and the community together but need to be embedded in existing community structures for sustainability.
Keywords: child survival; management strengthening